Seed quality and germination performance increase with cross-pollination in members of subtribe Orchidinae (Orchidaceae) - Bazzicalupo, Miriam; Masullo, Ilaria; Duffy, Karl J; Fay, Michael F; Calevo, Jacopo (Botanical journal of the Linnean Society, 2025)
Over half of angiosperms have self-incompatibility systems to avoid self-pollination and inbreeding depression. Many members of Orchidaceae are self-compatible, but they may be prone to negative consequences of self-pollination. We investigated the effects of both within-flower (autogamy) and within-plant (geitonogamy) self-pollination, and cross-pollination on fruit set, seed quality, and germination rates in 11 related orchid taxa of subtribe Orchidinae. We hand-pollinated flowers and measured fruit set to estimate pre- and postzygotic barriers. We collected morphometric data on embryos and seeds and calculated the percentage of seeds with embryos and seed viability. We then calculated inbreeding depression values for each treatment for each taxon. Ten taxa produced fruits when self-pollinated, but germination rates and seed size increased with cross-pollination. Higher seed viability was correlated with larger embryos/seeds. However, geitonogamous pollination generally resulted in the lowest seed quality compared with autogamy and cross-pollination, with high values of inbreeding depression being detected. Only seven of the 11 taxa (Anacamptis papilionacea, Himantoglossum adriaticum, Ophrys apifera, Ophrys bertolonii, Orchis patens subsp. brevicornis, Orchis provincialis, and Serapias vomeracea) were confirmed as self-compatible. These results show that cross-pollination improves overall seed quality, and that the assessment of self-compatibility in orchids should be based on postfruiting stages.